OsCERK1 plays a crucial role in the lipopolysaccharide‐induced immune response of rice. Issue 3 (30th November 2017) - Desaki, Yoshitake; Kouzai, Yusuke; Ninomiya, Yusuke; Iwase, Ryosuke; Shimizu, Yumi; Seko, Keito; Molinaro, Antonio; Minami, Eiichi; Shibuya, Naoto; Kaku, Hanae; Nishizawa, Yoko
Summary: Plant cell surface receptor‐like kinases (RLKs) mediate the signals from microbe‐associated molecular patterns (MAMPs) that induce immune responses. Lipopolysaccharide (LPS), the major constituent of the outer membrane of gram‐negative bacteria, is a common MAMP perceived by animals and plants; however, the plant receptors/co‐receptors are unknown except for LORE, a bulb‐type lectin S‐domain RLK (B‐lectin SD1‐RLK) in Arabidopsis. OsCERK1 is a multifunctional RLK in rice that contains lysin motifs (LysMs) and is essential for the perception of chitin, a fungal MAMP, and peptidoglycan, a bacterial MAMP. Here, we analyzed the relevance of OsCERK1 to LPS perception in rice. Using OsCERK1 ‐knockout mutants ( oscerk1 ), we evaluated hydrogen peroxide (H2 O2 ) production and gene expression after LPS treatment. We also examined the LPS response in knockout mutants for the B‐lectin SD1‐RLK genes in rice and for all LysM‐protein genes in Arabidopsis. Compared with wild‐type rice cells, LPS responses in oscerk1 cells were mostly diminished. By contrast, rice lines mutated in either of three B‐lectin SD1‐RLK genes and Arabidopsis lines mutated in the LysM‐protein genes responded normally to LPS. From these results, we conclude that OsCERK1 is an LPS receptor/co‐receptor and that the LPS perception systems of rice and Arabidopsis are significantly different.